The Role of BIM and Parametric Intelligence in Architectural Practice: A Study of Architects in Uttarakhand - Dhruv Agarwal; Ayushi Pundir (International Journal of Architectural Design and Planning, 2026)
Dehradun, the capital city of Uttarakhand, represents one of India’s youngest and most dynamic urban centers in Uttarakhand. Since its designation as the state’s capital, the city has experienced a rapid evolution in architectural development and construction technology. As urbanization and design demands increase, architectural practices in Dehradun and across Uttarakhand are progressively shifting from conventional methods toward advanced digital tools that promote precision, efficiency, and sustainable outcomes. Among these, Autodesk Revit and Rhino–Grasshopper stand out as two of the most significant and widely adopted software platforms. Revit, a Building Information Modeling (BIM) tool, emphasizes structured design documentation, accuracy, and multidisciplinary coordination, while Rhino–Grasshopper, a parametric and algorithmic design environment, prioritizes creativity, form exploration, and data-driven design logic. This research aims to identify the current role of BIM and Parametric Intelligence in Uttarakhand and evaluate their application, usability, and efficiency in architectural practice, particularly focusing on their impact on workflow, collaboration, cost-effectiveness, and design innovation. The study employs a survey-based methodology, collecting both quantitative and qualitative data from architects and architectural firms operating in and beyond Dehradun. Responses will provide insights into adoption levels, user satisfaction, skill requirements, and perceptions regarding the integration of these tools in real-world projects. Preliminary literature and existing studies indicate that Revit is more dominant in technical documentation and coordination, whereas Rhino–Grasshopper excels in conceptual flexibility and environmental performance modeling. The research further explores the potential of hybrid workflows, such as Rhino.Inside.Revit, to combine the creative freedom of parametric modeling with the accuracy of BIM systems. The originality and value of this study lie in its practitioner-oriented comparative analysis, emphasizing real experiences within the Indian architectural context. By understanding how professionals adopt and adapt these digital tools, particularly in a rapidly evolving urban setting like Dehradun, the study contributes to broader discussions on digital transformation and computational intelligence in architecture
Keywords: Architectural practice; Autodesk Revit; Building Information Modeling (BIM); Computational intelligence; Rhino–Grasshopper; Uttarakhand context Computational Intelligence; digital transformation; interoperability; parametric intelligence